HUBUNGAN ANTARA PERSEPSI TERHADAP RISIKO DENGAN PERILAKU AMAN BAGIAN PRODUKSI TERKAIT KEBIJAKAN K3 DI PT AVENTIS PHARMA - Charisa Mahda Kumala (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Workplace accidents are generally caused by two main things that unsafe behavior and unsafe conditions. Some people will receive a hazard as a real risk for them and try to avoid. Some more will acknowledge the risk but perceive it as a challenge to the ability that they have. This perception can lead to actions that are not safe in the face of danger and increases the likelihood of a person who had an accident. In this study aims to determine the corelation perceptions of risks associated with the safe behavior production conduct policy OSH in PT Aventis Pharma. This type of research is descriptive correlation with cross sectional approach. Sample studies using a total population of 30 workers. Instruments used in this study using a quisioner perceptions of risk variables and the dependent variable safe behavior safer behaviors related policies OSH production workers in PT Aventis Pharma. Univariate analysis showed that workers have a positive perception of the risks and safe behavior accordingly. Based on the results of analysis bivariate corelation with hypothesis testing has done, with Spearman Rank Test (r = 0.802) with a significance level of 0.05 it indicates that there is a corelation perceptions of risks associated with the safe behavior production workers conduct with policy of occupational safety and health in PT Aventis Pharma.